2020
DOI: 10.1136/bjsports-2020-102624
|View full text |Cite
|
Sign up to set email alerts
|

High hopes: lower risk of death due to mental disorders and self-harm in a century-long US Olympian cohort compared with the general population

Abstract: ObjectiveTo determine the risk of death due to prominent mental disorders, substance abuse, and self-harm among US Olympians compared with the general population.MethodsAll female (n=2301) and male (n=5823) US Olympians who participated in the summer or winter Games between 1912 and 2012 were followed until 2016. The National Death Index certified their vital statuses and causes of death. We performed a Standard Mortality Ratio (SMR) analysis for all causes studied and applied the years-saved (YS) method to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
(49 reference statements)
3
15
0
Order By: Relevance
“…As such, the current study corroborates the findings from one of the largest register studies in this field, examining all US Olympians (n = 8124) who participated in the Summer or Winter Games between 1912 and 2012. That study found that elite athletes have significantly lower risk of both mental health problems and suicide when compared to the general population (Duncombe et al, 2020). Extending on these findings of reduced risk of mental health problems and suicidality, the current study also found elite athletes reported significantly higher quality of life, more positive affect, less loneliness and insomnia, as well as fewer alcohol problems, when compared to the general student population.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As such, the current study corroborates the findings from one of the largest register studies in this field, examining all US Olympians (n = 8124) who participated in the Summer or Winter Games between 1912 and 2012. That study found that elite athletes have significantly lower risk of both mental health problems and suicide when compared to the general population (Duncombe et al, 2020). Extending on these findings of reduced risk of mental health problems and suicidality, the current study also found elite athletes reported significantly higher quality of life, more positive affect, less loneliness and insomnia, as well as fewer alcohol problems, when compared to the general student population.…”
Section: Discussionsupporting
confidence: 68%
“…While some studies have reported prevalence rates of mental disorders and substance use disorder to be higher or comparable to the general population (Schaal et al, 2011;Rice et al, 2016;Gouttebarge et al, 2019;Akesdotter et al, 2020;Purcell et al, 2020), other studies have found lower suicide rates when compared to the general population (Maron et al, 2014;Rao et al, 2015;Lehman et al, 2016). Similarly, in one of the largest studies in this field, a recent study of US Olympians found a lower risk of mental health problems and suicide for this group, compared to the general population (Duncombe et al, 2020). In a consensus statement from IOC, it was concluded than more studies with large reference groups were needed to address specific domains of mental health outcomes in elite athletes, and also to examine whether there may by gender-specific patterns in the associations between the amount of exercise and mental health indicators (Reardon et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…10 In addition to the benefits of exercise on mental health, athletes might have a lower risk of death from mental disorders than the general population. Duncombe et al 11 recently analyzed a cohort of former athletes who had participated in the Olympics between 1912 and 2012. Although there were some exceptions (notably shooters, who actually showed a trend toward a higher risk), this study found a 32% lower risk of death attributable to mental and eating disorders or to suicide in former athletes than in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of a lower risk of death from these conditions or from suicide in athletes was corroborated in subgroup analyses for individual sports such as athletics, rowing, or swimming (as well as for "all other sports" combined as a single category). 11 Whether the abovementioned benefits on mental health are generalizable to top-level sports, particularly those associated with repeated head impacts (eg, boxing, American football) is, however, less clear. In fact, individuals with a previous history of repeated head impacts have more depression symptoms and an impaired cognitive function compared with people without this history.…”
Section: Introductionmentioning
confidence: 99%
“…This function was then compared with the one based on the general population of the same age and sex, living in the same calendar period obtained through the national life tables. Then, we calculated the difference between the areas below both functions to estimate the number of years lost or saved due to ND or all causes of death altogether (Antero et al, 2018;Duncombe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%